Risiko usaha, rentabilitas dan permodalan sebagai variabel anteseden kesehatan bank buku 3 dan buku 4 di indonesia - Nelaini Ika Merty (Journal of Business & Banking, 2018)
The banking industry in a country must be sound because it can cause the country’s economy develope to be good. The purpose of this study was to analyze the signifi cance of the effect of liquidity risk, market risk, credit risk, operational risk, profi tability and capital simultenously and partially on the bank’s soundness. The population of this research is BUKU 3 and BUKU 4 banks in Indonesia which were taken using a purposive sampling. The secondary data were collected using documentain and analyzed by using multiple linear regression analysis. The results show that liquidity risk, market risk, credit risk, operational risk, profi tability, and capital simultenously have a significant effect on the bank’ soundness. Liquidity risk, market risk, credit risk, profi tability, and capital, partially, influence insignifi cantly. Operational risk has a signifi cant effect on the bank’s soundness of BUKU 3 and BOOK 4 banks. This study suggest that the bank industry manage operational risk well by minimizing operational costs and increase operating income so that bank’ soundness increases every year.